Loanwords and stylistics: on the gallicisms in Sir Gawain and the Green Knight - Maria Volkonskaya (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2013)
This article explores the way in which loanwords become incorporated into a recipient language. It concentrates on the interim period, the time between the borrowing of a new word from a donor language and its incorporation into a recipient language. During this period the new word still retains some of its “foreignness”, its associations with another language and culture, therefore its stylistic potential is enhanced. The material is taken from Sir Gawain and the Green Knight, an English poem written in the latter half of the 14th century, at the time of the greatest influx of French words into English. This article shows that the Gawain-poet uses gallicisms as an expressive part of his poetic technique due to their stylistic potential as what were at the time recent borrowings.